The Gay Men's Task Force: the impact of peer education on the sexual health behaviour of homosexual men in Glasgow - Williamson, L. (BMJ Group, 2001)
Objective: To assess the impact of a peer education intervention, based in the "gay" bars of Glasgow, which sought to reduce sexual risk behaviours for HIV infection and increase use of a dedicated homosexual men's sexual health service, and in particular increase the uptake of hepatitis B vaccination. Design: Self completed questionnaires administered to men who have sex with men (MSM) in Glasgow's gay bars. Subjects: 1442 men completed questionnaires in January 1999, 7 months after the end of the 9 month sexual health intervention. Main outcome measures: Self reported contact with the peer education intervention, reported behaviour change, and reported sexual health service use. Results: The Gay Men's Task Force (GMTF) symbol was recognised by 42% of the men surveyed. Among men who reported speaking with peer educators 49% reported thinking about their sexual behaviour and 26% reported changing their sexual behaviour. Logistic regressions demonstrated higher levels of HIV testing, hepatitis B vaccination, and use of sexual health services among men who reported contact with the intervention. These men were more likely to have used the homosexual specific sexual health service. Peer education dose effects were suggested, with the likelihood of HIV testing, hepatitis B vaccination, and use of sexual health services being greater among men who reported talking to peer educators more than once. Conclusion: The intervention had a direct impact on Glasgow's homosexual men and reached men of all ages and social classes. Higher levels of sexual health service use and uptake of specific services among men who had contact with the intervention are suggestive of an intervention effect. Peer education, as a form of health outreach, appears to be an effective intervention tool in terms of the uptake of sexual health services, but is less effective in achieving actual sexual behaviour change among homosexual men. Key Words: homosexual men; peer education; sexual behaviour; sexual health service use